Impact of Moon Phases on Purse Seine Fishing Yields in Bulukumba Waters - Caronge, Siti Adinda Dihar Indahwati; Palo, Mahfud; Nelwan, Alfa F.P.; Wiharto, Muhammad (Jurnal IPTEKS Pemanfaatan Sumberdaya Perikanan, 2024)
The activity of small pelagic fish is influenced by light, so changes in the moon phase will impact the distribution of fish, especially small pelagic fish. Therefore, this research aims to determine the concentration of fish based on lunar phases and explain the composition and frequency of fishing based on lunar phases in Bulukumba Regency. This research aims to provide information to fishermen to determine potential fishing areas. Data was collected in Bulukumba from July to September 2020 following 28 fishing trips using purse seines. The data used are primary and secondary. Primary data consists of the type and number of catches grouped based on lunar phases, namely dark, dark-to-light, light, and light-to-dark periods. Secondary data was obtained from interviews and literature studies. The data analysis used calculates the composition and frequency of catches. The results showed that there were eight types of fish caught during the research. The types of fish most commonly seen are trevally (Decapterus spp), yellow trevally (Selaroides sp), and mackerel (Rastrelliger spp). The highest catch frequency of these three types of fish occurred during the light-dark and light-dark periods.